Origination and evolution of point defects in AlN film annealed at high temperature - Kai, Cuihong; Zang, Hang; Ben, Jianwei; Jiang, Ke; Shi, Zhiming; Jia, Yuping; Cao, Xingzhong; Lü, Wei; Sun, Xiaojuan; Li, Dabing (Journal of luminescence, 2021)
While high temperature annealing has been proven to be an effective strategy to reduce threading dislocation density of AlN film, the point defect induced near-ultraviolet emission increases dramatically with the increase in annealing temperature, and thus limits its application in deep ultraviolet optoelectronic devices. Herein, the origination and evolution of point defects in high-temperature annealed AlN are studied and clarified by photoluminescence spectroscopy, secondary ion mass spectrometry, positron annihilation and first-principles calculation. We have confirmed that (1) the annealing induces the increased O impurity concentration by two orders of magnitude; (2) The increase of O impurity concentration in AlN after high temperature annealing is the key factor that causes the evolution of point defects and the enhancement of near ultraviolet defect peak; (3) the formation of more O content [VAl-n(ON)] and VN at different annealing temperatures are responsible for photoluminescence evolution. Present work reveals the formation mechanism of point defects in AlN and provides further support for improving the quality of AlN. •The O point defects increase during the high temperature annealing process.•The VAl-2(ON) and VN defects are responsible for photoluminescence evolution.•The optical transition energies was evaluated by DFT calculations.